Working with you is killing me : freeing yourself from emotional traps at work - Crowley, Katherine; Elster, Kathi (New York : Warner Business Books, 2006)
"I don't want to quit my job; I want to quit my manager (or coworker)." If this statement rings true to you, then this guide is exactly what you need to separate yourself from the toxic relationship that is ruining your job. The authors call the experience of being caught in an emotionally distressing situation at work being "hooked," and they provide tools to unhook physically, mentally, and emotionally. They define some of the roles that we play, such as hero, caretaker, rebel, martyr, peacemaker, or entertainer. Playing a role is a hook, too, because it holds us back from realizing our true potential. We naturally fall into certain roles, and the authors provide ways to break out of our comfort zone to expand and thrive at work. The guide is short on analysis and long on ideas and examples to help you survive in the often-claustrophobic space called "the office." Harvard-trained psychotherapist Crowley and small-business expert Elster are published authors, educators, consultants, and seasoned guides in the area of professional fulfillment through self-awareness.
Change your reaction, change your life -- The business of boundaries - protecting yourself at work -- If the role fits, you don't have to wear it -- Haven't we met before? Fatal attractions at work -- Managing up - taking control -- Difficult and extreme bosses - how to keep your sanity -- Managing down - business parenting -- Corporate culture - Is this the right place for you?
Includes index.
Keywords: Psychology, Industrial; Interpersonal relations; Interpersonal communication; Problem employees